Projekts Lauksaimniecības tehnikas "New Holland" servisa "AGROTEH" izveidošana - Saulīte, Dace (Latvijas Universitāte, 2009)
Projekta ideja ir izveidot jaunu lauksaimniecības tehnikas NEW HOLLAND servisa apkopes uzņēmumu, kura darbības rezultātā palielināsies šīs tehnikas īpašnieku apmierinātība, un tehnikas pārdošanas apjoms, tiks iegūta un nostabilizēta lielāka tirgus daļa. SIA Agroteh ilgtermiņa mērķis ir ar savu darbību palīdzēt nodrošināt mātes uzņēmumam ieņemt līderpozīcijas lauksaimniecības tehnikas tirgū, kurš nodarbojas ar NEW HOLLAND lauksaimniecības tehnikas tirdzniecību .

Project idea is to create a new service company for NEW HOLLAND agricultural machinery, whose activity as a result will increase satisfaction for machinery holders and will maximize realize amount of agricultural machinery , and in the end will acquired and become in stable market share. Ground on the being situation in the Latvia agriculture technique market, to produce a project, a new daughter's enterprise SIA Agroteh, which action include all Latvia regions and which can successful operate giving service in agriculture technique NEW HOLLAND service providing techniques service and repairs. Enterprise actions begin in November of 2008. The SIA Agroteh long-term purpose is with its action to help to provide a mother enterprise to take in a leading position in agriculture technique market mother enterprise, which is engaged in the NEW HOLLAND agriculture technique trade.
Project Agricultural machines "New Holland" service "AGROTEH" establishment
Keywords: Finanses un kredīts